Toronto's "Girl Workers." The Female Body and Industrial Efficiency in Her Own Fault - Lindsey, Shelley (Cinémas, 1995)
Her Own Fault is an instructional film produced by Ontario's Provincial Board of Health through its Division of Industrial Hygiene in 1921. In its attempt to influence Toronto's working women, the film suggests some of the challenges posed by the female factory worker in the early part of the century. This article will situate Her Own Fault in relation to othet contemporary discourse on women's work and leisure habits. The author will also consider the film's treatment of female factory workers and the ways in which this film might circumscribe net behaviour and net gaze.